Joyful Learning-Based Islamic Religious Education and Its Implications for Students’ Intrinsic Motivation - M Renaldy Fadillah; Neng Gina Aryani; Kahfi Pratama (Generasi Sains Indonesia, 2026)
This study aims to analyze the implementation of joyful learning in Islamic Religious Education and examine its implications for students’ intrinsic motivation in a fourth-grade classroom at Madrasah Ibtidaiyah Tegal. A qualitative case study approach was employed using classroom observations, semi-structured interviews, and documentation. The findings indicate that joyful learning creates an interactive, enjoyable, and student-centered learning environment through storytelling, educational games, collaborative activities, and dialogic communication. These instructional practices significantly enhance students’ intrinsic motivation, reflected in increased enthusiasm, curiosity, engagement, self-confidence, and learning satisfaction. The study also identifies teacher creativity, positive teacher-student relationships, and supportive classroom environments as key enabling factors. The findings imply that integrating emotionally meaningful learning experiences into religious education can improve instructional effectiveness and promote more humanistic, psychologically responsive educational practices at the primary level.